Biomechanics of Long Cane Use. (May 2019) - Wall Emerson, Robert; Kim, Dae Shik; Naghshineh, Koorosh; Myers, Kyle R.
Introduction: The modern long cane has been used by people who are blind for traveling for decades. This article describes parameters surrounding the collection of over 10, 000 trials of people walking with the long cane to detect drop-offs or obstacles. Methods: The data include 10, 069 trials representing 101 different participants in 366 conditions over 11 studies spanning the 9 years from 2007 to 2016. Each of the studies investigated different participant or cane characteristics or both in terms of their effect on either drop-off or obstacle detection. Results of detection performance in these studies appear in other articles. This article describes biomechanical measures derived from 3-D motion analysis equipment used during the studies. Results: Initial treatment of the large data set indicated that participants tended to not center their cane arc laterally on their body, deviating up to about 20 centimeters from midline. Arc widths averaged almost a meter, and arcs were generally centered. Participants were generally poor at being in step or having consistent rhythm. Coverage rates averaged about 85%. Discussion: Although participants might have demonstrated artificially high skill performance due to being in a research study, data do offer insights into mechanical performance of skills. This survey of the data set indicates that not centering the hand holding the cane does not decrease body coverage less than about 85%. However, further analyses will be conducted to delve more deeply into all aspects of the data. Implications for practitioners: Basic cane skills can be taught with short sessions and massed practice. Novices can acquire basic cane skills on par with cane users who are blind, but individual differences exist and the interplay of biomechanical variables needs to more fully understood.